Excellent long‐term patient and graft survival are possible with appropriate use of livers from deceased septuagenarian and octogenarian donors. Issue 9 (28th January 2014) - Chedid, Marcio F.; Rosen, Charles B.; Nyberg, Scott L.; Heimbach, Julie K.
Abstract Background Although increasing donor age adversely affects survival after liver transplantation, livers have been used from selected deceased donors older than 70 years. Although there are reports of excellent short‐term results, long‐term results are unknown. Our experience was reviewed with septuagenarian and octogenarian deceased donors to determine long‐term outcomes. Methods All primary deceased donor liver transplants performed at our institution between July 1998 and December 2010 were reviewed. Recipients of livers procured after circulatory arrest, split and reduced‐size livers and multiple organ transplants were excluded from the study. Patient and graft survival were calculated using the Kaplan–Meier method, and survival comparisons were made with the log‐rank test. Results In total, 780 patients met inclusion criteria, and 109 patients received livers from donors older than 70 years (range = 70–86). There were no differences in long‐term patient (P = 0.67) or graft (P = 0.42) survival between hepatitis C negative recipients of livers from older compared with younger donors. In contrast, 7‐year survival for HCV‐positive recipients of older donor livers was less than half that of HCV‐negative recipients. Discussion Transplantation of livers from septua‐ and octogenarian donors can achieve excellent long‐term patient and graft survival for selected HCV‐negative patients.